Emerging International Dimensions in East Asian Higher Education
XII, 261 p. 7 illus., 5 illus. in color.
Keywords: This book discusses emerging roles and functions of higher education and the implications for higher education as a public good in a context of globalization and regionalization. Increases in the mobility of students, faculty and researchers across national borders and in the number and variety of cross-border linkages among higher education institutions have challenged the understanding of higher education as a public good in a single nation. At the same time, the increased privatization and marketization brought by globalization have provided new opportunities and vulnerabilities in markets no longer defined solely by national borders and governed only by national policy. The financial crisis of 2008 underscored these vulnerabilities, highlighting both the inter-dependence of economies and institutions but also the increasing multi-polarities of influence in higher education. In parallel with increased student mobility globally is an increase in regional mobility of students, who are attracted to new centers of knowledge and research. As institutional quality is increasingly understood in a global context, universities from new regions of the world are moving to the top of world rankings at the same time that competition for students among lower ranking institutions has extended beyond traditional borders. In a variety of ways, individuals and institutions are increasingly looking to regional neighbors for students, opportunities for study, as well as instit utional partnerships and collaboration.